Strategy Development to Improve Brand Awareness and Sales Performance - Nofela, Nabilla Putri; Belgiawan, Prawira Fajarindra (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
The rapid growth of the beauty and skincare industry in Indonesia is driven by the extensive use of digital platforms for product promotion and marketing. Noera Beauty Care, a local beauty brand, faces challenges in enhancing its brand awareness and sales performance. This study aims to analyze the influence of digital marketing, content marketing, endorsement influence, and brand engagement on brand awareness and its impact on purchase intention. A mixed-method approach was employed, combining qualitative interviews with the CEO and head of marketing and quantitative surveys of 200 active social media users. The data were analyzed using PLS-SEM. The findings indicate that digital marketing, content marketing, and endorsement influence significantly impact brand awareness, while brand engagement does not. Brand awareness positively affects purchase intention. Based on these findings, several marketing strategies are proposed, such as product innovation through collaboration with influencers, creating live shopping or virtual try-on sessions, website updates and development, evaluation, and adjustment of marketing strategies, investing in IT infrastructure, strengthening relationships with consumers through loyalty programs, and creating educational content and quizzes to increase public knowledge about the benefits of Noera products.